Strategi Komunikasi Pemasaran Museum Private Tumurun Dalam Mempertahankan Kunjungan Wisatawan - Dewi, Rodhita Permana; Hindra H, Nurnawati; Widiyowati, Estu (Solidaritas, 2024)
Museums are often considered ancient and scary by some people because the atmosphere and place seem old school. However, several museums in Indonesia, including the Tumurun Private Museum, have succeeded in changing this view by presenting interesting collections of modern and contemporary art. This museum is not only intended as a place to store works of art, but also as an educational venue and to introduce local artists to the millennial generation. This research aims to identify the marketing communication strategies used by the Tumurun Private Museum to maintain its attractiveness to visitors. Researchers used descriptive qualitative research methods with data collection techniques of observation, documentation, interviews and surveys. In collecting data, researchers conducted interviews with assistant managers and tour guides as managers and employees who took part in implementing marketing communication strategies in maintaining tourist visits at the museum and conducted interviews with visitors using the purposive sampling method. Based on the results of research analysis, the management of the Tumurun Private Museum carries out marketing communication strategies to maintain tourist visits to the museum, namely by advertising, Sales Promotion, Public Relations, Personal Selling and Events. Experiences (event experience). The conclusion of this research is that with the marketing communication strategy carried out by the museum management, the Tumurun Private Museum succeeded in maintaining tourist visits. This is evident from the fact that many people are starting to know about the Tumurun Private Museum, which has attracted their interest in visiting the museum. This shows that the right communication strategy can bring success in attracting and retaining visitors. Keywords: Marketing communication strategies, Integrated Marketing Communication, Tumurun Private Museum.